2020
DOI: 10.1101/2020.12.02.402354
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Novel Role for Nucleolin in Splice Site Selection

Abstract: Latent 5’ splice sites are highly abundant in human introns, yet, are apparently not normally used. Splicing at most of these sites would incorporate in-frame stop codons generating nonsense mRNAs. Importantly, under stress and in cancer, splicing at latent sites is activated generating nonsense mRNAs from thousands of genes. Previous studies point to an unresolved RNA quality control mechanism that suppresses latent splicing independently of NMD. They further demonstrated a pivotal role for initiator-tRNA in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…NCL in the nuclear speckles colocalizes with SC35 (as we also observe in our study), and is reported to interact with the pre-catalytic spliceosome complex and regulate AS of fibronectin ( 80 ). NCL is also known to play a major role in splice site selection ( 81 ). qRT-PCR performed to detect exon inclusion events for selected transcripts established the role of rG4s in AS.…”
Section: Discussionmentioning
confidence: 99%
“…NCL in the nuclear speckles colocalizes with SC35 (as we also observe in our study), and is reported to interact with the pre-catalytic spliceosome complex and regulate AS of fibronectin ( 80 ). NCL is also known to play a major role in splice site selection ( 81 ). qRT-PCR performed to detect exon inclusion events for selected transcripts established the role of rG4s in AS.…”
Section: Discussionmentioning
confidence: 99%